The Development of a Physics Module Based on the SETS Learning Model to Improve Students' Conceptual Understanding - Miftahul Jannah Fitri; Silvi Trisna; Iing Rika Yanti (JIPF (Jurnal Ilmu Pendidikan Fisika), 2021)
This study aims to produce a learning device in the form of a physics module based on SETS that is valid and practical to improve students' conceptual understanding. The type used in this research is Research and Development (R&D). Subjects of this study were teacher and students of class XI MIA 1 with a total of 31 subjects. The research procedure  is the 4-D model, namely define, design, develop, and disseminate. Due to time and cost limitations, this  research is limited to the develop stage. The research instrument used was a validity questionnaire, practicality, and a description of the conceptual understanding. Furthermore, data obtained were analyzed to see the validity and practicality of the module as well as an assessment of students' conceptual understanding of dynamic fluid material. The level of understanding of students' concepts is seen from the aspects of interpretation, exemplifying, explaining, and comparing. The results showed that the physics module based on the SETS developed was categorized as very valid with an average of 82.16 and in the very practical category with a percentage of 84.29. Then for understanding the concept of students obtained a score of 94.67 in the interpretation  aspect,  86.98 in the exemplary aspect, then 81.10 and 86.61 respectively for the aspects of explaining and comparing. Learning using a physics module based on SETS is very good to be applied in order to improve students' conceptual understanding of dynamic fluid material. This was proven by the increase in students' understanding of concepts in every physics learning meeting on dynamic fluid material.